The Meaning of “Independent Learning” in Curriculum Planning under the Merdeka Curriculum at the Senior High School Level - Maulana Iqbal Mahendra; Daud Hizbalhaq Addamawi; Andryan Verly Dwi Pratama; Irwan Efendi; Gina Muta'affif (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2026)
A significant educational revolution in Indonesia, the Merdeka Curriculum is intended to address the learning crisis and fulfill the needs of 21st-century skills. The execution of this curriculum at the senior high school (SMA) level faces particular difficulties due to the developmental characteristics of students and the growing complexity of subject specialisation. With a special emphasis on lesson module creation, diagnostic assessment, and the Project for Strengthening the Pancasila Student Profile, this study seeks to examine how the idea of "independent learning" is understood and put into practice in curriculum planning at the senior high school level under the Merdeka Curriculum. The methodology utilized in this research was qualitative, using a phenomenological research design. School headmasters, topic teachers in Grades X and XI, and older high school students who had put the Merdeka Curriculum into practice made up the majority of the group. In addition to lesson modules, learning objective sequences, and school operational curriculum materials, the data were obtained through thorough interviews and document analysis. The interactive approach to data analysis included data reduction, data visualization, and conclusion creation. The results reveal that, even though teachers generally believe that the Merdeka Curriculum offers pedagogical flexibility, they continue to have considerable problems translating this flexibility into systematic curriculum planning. The integration of the Pancasila Student Profile initiatives into the fundamental instructional activities, the use of diagnostic evaluation to promote differentiated learning, and the creation of competency-based course modules are all challenges. To ensure that the Merdeka Curriculum is implemented effectively at the senior high school level, these results emphasize the necessity of ongoing professional development and pedagogical coaching.